Methodological considerations for circulating long noncoding RNA quantification. Issue 8 (August 2022) - de Gonzalo-Calvo, David; Sopić, Miron; Devaux, Yvan; ,
Abstract : In the past decade, significant resources have been invested in long noncoding RNA (lncRNA) research. Despite the knowledge available, we are far from incorporation of lncRNA into clinical practice. Here, we emphasize the technical challenges in the field, hoping to provoke a response leading to new consensus and guidelines.